DEVELOPMENT OF TECHNOLOGY FOR PRODUCTION OF PECTIN PRODUCTS FROM GRAPE POMACE OF DIFFERENT VARIETIES - Natalia Sergeyevna Limareva; Alena Vladimirovna Mityanina; Lyudmila Vladimirovna Donchenko (Современная наука и инновации)
Article presents the results of a study to determine the optimal parameters of the process of obtaining pectin extracts from thepomace of different grape varieties grown in the Stavropol region.